Ac'cent makes food flavors sing - International Minerals and Chemical Corporation (1948)
Advertising brochure for Ac'cent, a pure mono sodium glutamate (MSG) food additive product manufactured by the Amino Products Division of the International Minerals & Chemical Corporation.
Keywords: Food additives; Food additives industry; Monosodium glutamate; International Minerals and Chemical Corporation; Advertising